Environmental co-operation and institutional change : theories and policies for European agriculture - Hagedorn, Konrad (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2002)
Addressing the value of co-operative strategies to achieve sustainable development and cope with agri-environmental problems, this book should be of specific interest to agricultural economists and those with an interest in ecological reforms of agricultural policies.
Includes bibliographical references and index.
oif 08/08/16, ijb 09/04/2019
Loan
Keywords: Environment; Agriculture; Agricultural ecology; Agriculture and state; Sustainable development